DIFFERENCES OF MANUAL NATIONAL EXAM AND COMPUTER BASED NATIONAL EXAM (UNBK) USING COMPARISON OF SCORES AND PUBLIC PERCEPTIONS - Nestiyanto Hadi; Dwi Kartika Susanti; Muhamad Rais (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The government held a national exam every year as a learning evaluation tool. The general public gave many responses to the implementation of the national exam. There are people who are satisfied and there are also people who are not satisfied. The factors that cause public dissatisfaction are the leaked problem test and massive acts of cheating. The government took the initiative to change the mechanism of the national exam which originally used the computer answer sheet (manual) to be computer-based (UNBK). This study's purpose is to determine whether there are differences between the implementation of the manual and computer-based national exam. The research method used descriptive analysis based on the data of the acceptance scores of new high school (SMA) students and the questionnaires. The conclusion is there are differences between the implementation of manual and computer-based national exam. The mean value of UNBK is lower with the standard deviation value greater than the manual national exam. It can show that the scores obtained by participants is not uniform and can be an indication that the government is able to minimize the leaked problem test and cheating action. In line with the public perception that more than 60% agree that the final score of UNBK shows the results of honest and fair learning evaluation.